Ethnobotany at a local scale: diversity of knowledge of medicinal plants and assessment of plant cultural importance in the Polokwane local municipality, South Africa. Issue 1 (2nd January 2017) - Leso, Lesetsa Kennedy; Elansary, Hosam O.; Mearns, Kevin; Yessoufou, Kowiyou
Abstract: Unravelling the pattern of traditional plant usages in a society is necessary to inform interventions for biodiversity conservation. In the present study, we documented traditional knowledge of plant usages and analysed the pattern of culturally important plants along a phylogeny of South Africa's medicinal plants. Data were collected through interviews, field visits and group discussions, and cultural importance was assessed using two metrics: use value (UV s ) and quality use value of species (QUV s ). K statistic was used to assess how UV s and QUV s values are distributed on a phylogeny. Overall, 50 medicinal plant species in 35 botanical families were reported. Fabaceae and Celastraceae contain more medicinal species than any other family, perhaps because of a wider distribution in the study area. Although there was no evidence that knowledge of medicinal uses varies significantly according to informant status, sex, ethnic group and age category, or residence time of the informant in the study area, traditional healers show a wider range of medicinal knowledge than any other informants. Culturally important plants are not significantly clustered on the phylogeny, suggesting a priori a limited value of phylogeny in identifying culturally valuable plants. However, this potential limitation could be driven by the local focus of the present study. We call for further investigations at a broader scale to establish potential phylogenetic signals in plant cultural importance.